Professor bacharel iniciante no ensino superior: dificuldades e possibilidades pedagógicas. - Aires, Susye Nayá Santos (2015)
The present study investigates the teaching practice of the beginning teacher in higher education. The aim was to identify and analyze learning acquisitions, tensions and difficulties frequently faced by those whose first professional training was not that of a teacher, but have recently taken up a teaching position. The research is based on four axes: higher education, BA teacher, early years in the profession and teacher education. As theoretical-methodological resources, we began with bibliographic research on the CAPES and ANPED official websites, and SCIELO articles database, starting from papers written by the most prominent researchers on the topic. In order to substantiate the teacher training subtopic, we resorted to authors such as Franco, Pimenta, Anastasiou; to early career, to Masetto and Guarnieri; and, to higher education, to Masetto, Pimenta and Veiga. This is a qualitative research, with collection of data through questionnaires, and semi-structured interviews. Twelve teachers from higher education private institutions participated in this study. Data analysis was based on Ghedin, Franco and Minayo, and the dialectical-hermeneutical method was used as referential. Results showed that BA-teachers, due to the lack of previous training, initially tend to prioritize the content-related aspects of the subject they are dealing with, transforming the act of teaching into a simple transmission of information. However, as their careers evolve, these teachers manage to acquire a few teaching skills and strategies that favor their teaching practice. For these teachers, both institutional reception and talk to peers have proved to be important aspects that contributed to their professional socialization. They mentioned initial problems such as lack of interest from students, the effort to gain students attention and the lack of time to seek for proper pedagogical training. Results also showed and reinforced the need to continuous education for BA-teachers, not only within the university walls, but also with post-graduate stricto sensu programs, such as Masters in Education ¿ ME, once this is a core requirement to the improvement and quality of the teaching practice of beginning teachers in higher education. It is also considered that pedagogical knowledge, continuous education and its professionalization must be the set of competences which are necessary to the performance of this activity.